PENGARUH PAJAK, PENANAMAN MODAL DALAM NEGERI (PMDN) DAN TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Melni Yunita; Sri Ulfa Sentosa (Universitas Negeri Padang, 2019)
This study aims to determine the effect simultaneously or partially between tax, investment (PMDN) and labor towards economic growth in Indonesia. The type of data in this study is secondary data and time series data in the form of annual data from 1987 to 2017, the analysis technique used in this study is multiple linear regression. Based on the results of testing, simultaneously tax, investment (PMDN) and labor have a significant effect on economic growth in Indonesia from 1987 to 2017. Partially the tax variable has a significant positive effect, investment (PMDN) has a significant positive effect, labor has a significant positive effect towards economic growth in Indonesia from 1987 to 2017. In the future, it is recommended that policy makers, especially the government, must maximize national tax acquisition as a source of development costs. Increasing the value of investment in Indonesia by providing better security guarantees to investors, simplifying the licensing process and keeping the Indonesian economy stable and conducive. In addition, increasing the capacity and skills of the workforce is also very necessary given the increasingly global competition and as an effort to attract third parties to come to areas that have high capacity resources.